TRANSFORMATION OF THE PROCUREMENT SYSTEM IN THE INDONESIAN GOVERNMENT - Firmansyah, Anry; Maulana, Rio Yusri; Miftah, Ahmad Zaini (Universitas Padjadjaran, 2024)
The transformation of Indonesia's procurement system has become a strategic step to improve governance's effectiveness, transparency, and accountability. In this article, we discuss the shift of the procurement system from corruption-prone manual methods to digitalization through e-procurement and e-catalog. This transformation started with bureaucratic reform after 1998, the creation of LKPP, and the implementation of digital systems such as SPSE, SiRUP, and e-catalog. Kurt Lewin created the framework of the Theory of Organizational Change, which includes three stages: unfreeze (making aware of the need for change), change (making changes), and refreeze (creating new norms). This framework was used to analyze this transformation. This model helps us understand how procurement systems are systematically changed, from finding inefficiencies to making digitalization the new standard in governance. The online content analysis method was used in this research. It combines data from digital platforms, academic reports, government documents, and online media articles. The data was analyzed using coding and interpretation methods to find key issues and evaluate how effective the changes to the procurement system were. This method enabled an in-depth understanding of how Indonesia's procurement system is changing. The results show that the transformation requires a holistic approach to ensure sustainability, including regulatory changes, the creation of a blockchain-based system, HR capacity building, and improved evaluation. By combining organizational change theory and a comprehensive methodology, the transformation will become the norm in procurement governance and help sustainable domestic economic growth.